Fast Detection of Uric Acid in Urine for Early Diagnosis Using THz Polarized Waves - Zahra Mazaheri; Giorgia Federico; Can Koral; Gian Paolo Papari; Lakshmi Ullatil; Paolo Russo; Antonello Andreone (Sensors)
Towards new and improved techniques in liquid biopsy for the diagnosis of diseases, this study reports experimental evidence of a rapid and reliable method based on terahertz (THz) time-domain spectroscopic ellipsometry (TDSE) for the early diagnosis of kidney-related diseases, using the detection of uric acid (UA) content in urine. Employing a custom-built THz-TDSE system, we analyzed the absorption and dispersion response of synthetic urine samples with varying concentrations of UA. The technique provides a prompt indication of UA presence and concentration, thanks to the sensitivity of THz waves to intermolecular interactions such as hydrogen bonding. The results clearly show a linear correlation between the UA concentration and changes in the absorption spectra of urine in the frequency window 0.2–1.2 THz, with the minimum detectable UA concentration being approximately close to the upper limit of normal UA levels in urine. The increase in the absorption coefficient as a function of the UA concentration provides a means for a quantifiable measure of the UA biomarker in urine for assessing disease stage. This study proves that THz-TDSE is capable of detecting UA at concentrations relevant for early-stage diagnosis of renal diseases, with an estimated sensitivity of 0.2 g/L in the region where the material response is linear.